2019
DOI: 10.1038/s41391-019-0195-5
|View full text |Cite
|
Sign up to set email alerts
|

A review of prostate cancer treatment impact on the CNS and cognitive function

Abstract: Background Androgen deprivation therapy (ADT) is the backbone of systemic therapy for men with prostate cancer (PC); almost one-half of patients receive treatment during their disease course. However, a range of cognitive and other central nervous system (CNS) changes have been associated with ADT. In this review, we discuss extant data describing these complications and the mechanisms through which medications used to deliver ADT may affect them. Methods We performed a MEDLINE search for appropriate papers pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 74 publications
2
87
3
1
Order By: Relevance
“…[11][12][13] Rates of central nervous system related AEs vary among the SGARIs due to different penetration of the bloodbrain barrier. 19 Given that nmCRPC is fairly asymptomatic, an important treatment goal is to minimize AEs, as they can interfere with patients' daily activities, affecting quality of life (QoL), and may lead to treatment discontinuation. 20 Hence, careful weighing of the efficacy and AEs of treatment is crucial in nmCRPC treatment decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Rates of central nervous system related AEs vary among the SGARIs due to different penetration of the bloodbrain barrier. 19 Given that nmCRPC is fairly asymptomatic, an important treatment goal is to minimize AEs, as they can interfere with patients' daily activities, affecting quality of life (QoL), and may lead to treatment discontinuation. 20 Hence, careful weighing of the efficacy and AEs of treatment is crucial in nmCRPC treatment decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…ADT was not associated with an increased risk of cognitive impairment than patients with PCa who had not received ADT in the general population [ 55 ]. A systematic review and a meta-analysis of cognitive impairment in men with PCa receiving ADT also found no statistically significant risk of overall cognitive impairment after ADT [ 20 , 56 ]. As in these studies, we detected no statistically significant decreases of the cognitive performance in the sample, but this finding should be considered cautiously, as the decline of the scores might need a bigger sample size or a longer period to appear.…”
Section: Discussionmentioning
confidence: 99%
“… 62 CNS exposure to AR antagonists is postulated to produce cognitive deficits and fatigue. 63 Furthermore, negative feedback on the GnRH axis results in testosterone upregulation and increased estrogen levels (via peripheral aromatization) which eventually leads to gynecomastia and breast tenderness. 64 Darolutamide, a third-generation AR antagonist, does not appear to suffer from this pharmacokinetic limitation with a distinct chemical structure that likely restricts blood–brain barrier penetration and binding affinity for γ-aminobutyric acid type A receptors.…”
Section: Future Applications Of Enzalutamide In Cspc: a Review Of Ongmentioning
confidence: 99%